PENGARUH METODE QIRO'ATI TERHADAP KETEPATAN BACAAN MAD TABI'I SISWA KELAS V SD NEGERI 30 SUNGAILIAT - Sri Mulyani; Adi Saputra; Rifki Hanif Setiawan (STKIP Subang, 2026)
This study was conducted in response to the low accuracy of Mad Tabi’i recitation among fifth-grade students at SD Negeri 30 Sungailiat. Preliminary and subsequent observations revealed that the majority of students experienced difficulties in distinguishing between long and short vowel sounds in accordance with tajwid rules. Therefore, this research aimed to examine the effect of the Qiro’ati method on the accuracy of students’ Mad Tabi’i recitation. This study employed a quantitative approach with an experimental design, specifically the One-Group Pretest–Posttest Design. The population consisted of 34 students, while the sample comprised 27 students selected through purposive sampling. Data were collected using an oral test designed to assess the accuracy of students’ Mad Tabi’i recitation. Data analysis was carried out using the Shapiro–Wilk normality test and the Paired Sample t-test with the assistance of SPSS version 22. The results showed that the average pretest score was 43.70 and the posttest score increased to 58.11, indicating an improvement in the accuracy of students’ Mad Tabi’i recitation. The normality test results showed that the data were normally distributed with significance values of 0.067 for the pretest and 0.091 for the posttest. The hypothesis testing showed that the t-count value is 14.590, which was greater than the t-table value of 1.706 (0.000 < 0.05), so the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Thus, it could be concluded that the Qiro’ati method had a significant effect on the accuracy of Mad Tabi’i recitation of fifth-grade students at SD Negeri 30 Sungailiat.